2006
DOI: 10.1172/jci27794
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1 coactivators: inducible regulators of energy metabolism in health and disease

Abstract: Members of the PPARγ coactivator-1 (PGC-1) family of transcriptional coactivators serve as inducible coregulators of nuclear receptors in the control of cellular energy metabolic pathways. This Review focuses on the biologic and physiologic functions of the PGC-1 coactivators, with particular emphasis on striated muscle, liver, and other organ systems relevant to common diseases such as diabetes and heart failure.Members of the nuclear receptor (NR) superfamily relay physiologic and nutritional cues to critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
965
2
20

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,242 publications
(1,025 citation statements)
references
References 88 publications
38
965
2
20
Order By: Relevance
“…In various reports, CR enhanced mitochondrial biogenesis in several tissues (Nisoli et al ., 2005; Finck & Kelly, 2006). Two long‐lived strains, FIRKO and β/β mice, showed, compared with WT mice, decreased adiposity and enhanced mitochondrial biogenesis in WAT (Chiu et al ., 2004; Katic et al ., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In various reports, CR enhanced mitochondrial biogenesis in several tissues (Nisoli et al ., 2005; Finck & Kelly, 2006). Two long‐lived strains, FIRKO and β/β mice, showed, compared with WT mice, decreased adiposity and enhanced mitochondrial biogenesis in WAT (Chiu et al ., 2004; Katic et al ., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…PGC‐1α serves as a master inducer of mitochondrial biogenesis through its co‐activation of nuclear respiratory factors (NRFs), which control the expression of nuclear genes encoding mitochondrial proteins (Wu et al ., 1999; Finck & Kelly, 2006). Using adipogenesis array, we previously reported that in HGPS adipocytes, PGC‐1α was the most severely downregulated gene among the 84 genes involved in energy metabolism (Xiong et al ., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in humans and rodents have demonstrated that altered PPARGC1A signaling leads to insulin resistance, as recently reviewed. 21 Moreover, PPARGC1A is highly inducible in the liver and heart in response to physiological conditions that demand increased mitochondrial energy production. 21 PPARGC1A interacts with TFAM, which is required for the replication and maintenance of mtDNA.…”
Section: Resultsmentioning
confidence: 99%
“…21 Moreover, PPARGC1A is highly inducible in the liver and heart in response to physiological conditions that demand increased mitochondrial energy production. 21 PPARGC1A interacts with TFAM, which is required for the replication and maintenance of mtDNA. 22 Therefore, to determine whether the status of liver DNA methylation of these two genes was associated with peripheral insulin resistance, we measured the level of DNA methylation of three putative methylation target sites (CpG) in the promoters of PPARGC1A (located at positions relative to TSS: À513, À519, and À615) and Tfam (located at positions relative to TSS: À433, À442, and À499).…”
Section: Resultsmentioning
confidence: 99%